Awareness of climate risks and opportunities: empirical evidence on determinants and value from the US and European insurance industry - Gatzert, Nadine; Reichel, Philipp (Geneva Papers on Risk and Insurance: Issues and Practice, 2021)
In this paper, we study the awareness of European and U.S. insurance companies of climate-related risks and opportunities using a respective indicator from the Refinitiv Eikon database that uses reporting data. Based on this, we examine the determinants and value of the awareness of business risks and opportunities resulting from climate change, which, to the best of our knowledge, has not been done so far, despite its increasing and specific relevance for the insurance industry. We use a logistic regression analysis as well as a linear fixed effects model for a 10-year period from 2009 to 2018. Our results show that larger European insurers are significantly more likely to exhibit such awareness. When controlling for subsectors, property & casualty insurers tend to be aware of the risks and opportunities resulting from climate change. Moreover, when using the linear fixed effects model, we find a statistically significant positive value effect on Tobin's Q.
CRIS-Team WoS Importer:2021-05-21